Building capacity without disrupting health services: public health education for Africa through distance learning - Igumbor Ehi; Alexander Lucy; Sanders David (BMC, 2009)
Abstract The human resources crisis in Africa is especially acute in the public health field. Through distance education, the School of Public Health of the University of the Western Cape, South Africa, has provided access to master's level public health education for health professionals from more than 20 African countries while they remain in post. Since 2000, interest has increased overwhelmingly to a point where four times more applications are received than can be accommodated. This home-grown programme remains sensitive to the needs of the target learners while engaging them in high-quality learning applied in their own work contexts. This brief paper describes the innovative aspects of the programme, offering some evaluative indications of its impact, and reviews how the delivery of text-led distance learning has facilitated the realization of the objectives of public health training. Strategies are proposed for scaling up such a programme to meet the growing need in this essential area of health human resource capacity development in Africa.